2014
DOI: 10.1016/j.otsr.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Should distal radioulnar joint be fixed following volar plate fixation of distal radius fracture with unstable distal radioulnar joint?

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Distal radius fracture associated with distal radioulnar joint instability or radiocarpal joint dislocation was more complicated and tended to be operated on. Although there was still much debate about whether early surgery was necessary for the instability of distal radioulnar joint, the first thing we needed to do was to stabilize the distal radius fracture by operation. However, we also found that the presence of an associated ulnar styloid fracture did not influence the decision to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Distal radius fracture associated with distal radioulnar joint instability or radiocarpal joint dislocation was more complicated and tended to be operated on. Although there was still much debate about whether early surgery was necessary for the instability of distal radioulnar joint, the first thing we needed to do was to stabilize the distal radius fracture by operation. However, we also found that the presence of an associated ulnar styloid fracture did not influence the decision to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Plate fixation maintains the accurate reduction of DRFs, which may reduce the risk of post-traumatic ulnar impaction syndrome caused by distal radial malunion. In addition, recent reports of the treatment of DRFs by plate fixation support the notion that USFs or acute distal radioulnar joint laxity due to a TFCC tear do not have adverse effects on wrist function or pain (Kim et al, 2010Liu et al, 2014;Souer et al, 2009;Zenke et al, 2009). However, the natural history and factors associated with USWP after surgical treatment of DRFs have not been well addressed.…”
Section: Introductionmentioning
confidence: 99%